2019
DOI: 10.2147/ott.s196832
|View full text |Cite
|
Sign up to set email alerts
|

<p>INPP4B inhibits cell proliferation, invasion and chemoresistance in human hepatocellular carcinoma</p>

Abstract: Background: Inositol polyphosphate 4-phosphatase type II (INPP4B) has been identified as a negative regulator of phosphatidyl inositol 3-kinase (PI3K)/Akt signaling in human several cancers. However, the expression, clinical significance and biological function of INPP4B in human hepatocellular carcinoma (HCC) clinical tissues and cell lines are little known. Materials and methods: We evaluated the expression of INPP4B in 86 cases of paired human HCC samples by immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…5b, c ). In the human liver, INPP4B was detected in the cytoplasm and cell membrane of normal hepatocytes and its protein levels decreased in primary and, especially, metastatic hepatocellular carcinoma 37 , which undergo significant metabolic reprogramming. Similar to the mouse liver, hepatic INPP4B expression in patients with NAFLD was significantly reduced compared to healthy controls (GSE126848) 38 and there was a highly significant correlation between steatosis score and INPP4B mRNA levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5b, c ). In the human liver, INPP4B was detected in the cytoplasm and cell membrane of normal hepatocytes and its protein levels decreased in primary and, especially, metastatic hepatocellular carcinoma 37 , which undergo significant metabolic reprogramming. Similar to the mouse liver, hepatic INPP4B expression in patients with NAFLD was significantly reduced compared to healthy controls (GSE126848) 38 and there was a highly significant correlation between steatosis score and INPP4B mRNA levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5a, b and Supplementary Data 2 ). Lipid metabolism and peroxisome biogenesis are known targets of the PPAR family of transcription factors 37 , 39 , 40 . PPARG is a transcriptional regulator of fatty acid uptake and storage, while PPARA activity stimulates fatty acid oxidation 41 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggested that INPP4B is involved in the apoptosis of tumor cells [15,30]. The apoptosis levels of different lentivirus infection GBC-SD and SGC-996 cells were analysed by ow cytometry.…”
Section: Inpp4b Regulates Gbc Cells Apoptosis In Vitromentioning
confidence: 99%
“…Recently, Inositol polyphosphate-4-phosphatase type II (INPP4B), as a phosphoinositide phosphatase, has been proved to be a negative regulator of the PI3K-Akt signaling and plays a role of tumor suppressor gene (TSG) [9][10][11][12]. Low expression of INPP4B in several type of cancers is associated with poor clinical outcomes [13][14][15]. Knockdown of INPP4B could enhance breast cancer, melanoma and prostate cancer cell lines proliferation and migration, suggesting its TSG role in these cancer cells [11,15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation